Magnetic focus therapy (mft): a spiritual-somatic approach for trauma recovery in islamic counseling - M. Fahli Zatrahadi; Ifdil Ifdil (Asian Journal of Islamic Studies and Society, 2025)
Trauma remains a pervasive psychological challenge, particularly among Muslim individuals whose cultural and spiritual frameworks shape how distress is experienced and expressed. Conventional trauma interventions, largely derived from Western secular paradigms, often fail to address the embodied and spiritual dimensions of healing within Islamic contexts. This study introduces and examines the preliminary effectiveness of Magnetic Focus Therapy (MFT), a novel spiritual-somatic intervention that integrates body memory principles with Islamic counseling values. Employing a Single-Subject Research (SSR) A-B-A design, three Muslim clients in Pekanbaru, Indonesia presenting with diverse trauma backgrounds including bereavement, bullying, and family-related distress received three structured MFT sessions incorporating dhikr grounding, Qur'anic reflection, and tawakkul meaning reconstruction. Dependent variables included self-reported anxiety, body tension, negative thoughts, and emotional distress, assessed using a 0–10 rating scale at each phase. Visual analysis of data across the A1 (baseline), B (intervention), and A2 (follow-up) phases revealed consistent and clinically meaningful reductions across all four indicators for each client, with average reductions ranging from 57% to 75%. Social validation data further corroborated these gains, with clients reporting improved emotional regulation, spiritual calmness, and reduced somatic tension. These findings provide initial empirical support for MFT as a culturally responsive, brief, and structured trauma intervention suitable for Islamic counseling settings. Implications for Islamic psychotherapy, embodied counseling practice, and future research directions are discussed.